Mutation analysis of Leber's hereditary optic neuropathy using a multi-gene panel - Dai, Yu; Wang, Chenghui; Nie, Zhipeng; Han, Jiamin; Chen, Ting; Zhao, Xiaoxu; Ai, Cheng; Ji, Yanchun; Gao, Tao; Jiang, Pingping (Biomedical reports, 2018)
The present study investigates the spectrum and incidence of mitochondrial DNA (mtDNA) mutations associated with Leber's hereditary optic neuropathy (LHON) in a Han population using a multi-gene panel with 46 LHON-associated mutations among 13 mitochondrial genes. A total of 23 mutations were observed in a cohort of 275 patients and 281 control subjects using multi-gene panel analysis. The causative mutations associated with LHON were identified to be m.11778G>A, m.14484T>C, m.3460 G>A, m.3635G>A, m.3866T>C and m.3733G>A, responsible for 70.55% cases in the patient cohort. The secondary mutations in the Chinese LHON population were m.12811T>C, m.11696 G>A, m.3316G>A, m.3394T>C, m.14502T>C, m.3497C>T, m.3571C>T, m.12338T>C, m.14693A>G, m.4216T>C and m.15951A>G, with incidences of 5.09, 4.36, 4.00, 4.00, 4.00, 2.55, 1.82, 1.82, 1.45, 1.09 and 1.09%, respectively. Besides three hotspot genes, MT-ND1, MT-ND4 and MT-ND6, MT-ND5 also had a high incidence of secondary mutations. Those mutations reported as rare causative mutations in a European LHON population, m.3376G>A, m.3700G>A and m.4171C>A, m.10663T>C, m.13051G>A, m.14482C>G/A, m.14495A>G and m.14568C>T were undetected in the present study. The primary and secondary mutations associated with LHON in the present multi-gene panel will advance the current understanding of the clinical phenotype of LHON, and provide useful information for early diagnosis.